Cognitive Telerehabilitation for Older Adults With Neurodegenerative Diseases in the COVID-19 Era: A Perspective Study - Bernini, Sara; Stasolla, Fabrizio; Panzarasa, Silvia; Quaglini, Silvana; Sinforiani, Elena; Sandrini, Giorgio; Vecchi, Tomaso; Tassorelli, Cristina; Bottiroli, Sara (Frontiers in Neurology, 2021)
The COVID-19 pandemic is a global health problem that is radically transforming public and private healthcare organizations around the world, negatively affecting the rehabilitative treatments of non-COVID pathologies as well. In this situation, it becomes crucial to be able to guarantee the continuity of care also to all those patients with neurodegenerative diseases unable to reach healthcare services. Remote communication technologies are gaining momentum as potentially effective options to support health care interventions – including cognitive rehabilitation – while patients can stay safely at home. In this context, we are implementing HomeCoRe (i.e., Home Cognitive Rehabilitation software) in order to offer an innovative approach and a valid support for home-based cognitive rehabilitation in neurodegenerative diseases, such as mild cognitive impairment and early dementia. HomeCoRe has been developed within a research project between engineers and clinicians in order to obtain a usable and safe cognitive rehabilitation tool. This software has multiple advantages for patients and therapist over traditional approaches, as resulted from its use in hospital setting. HomeCoRe could then represent an opportunity for accessing cognitive rehabilitation in all those situations where patient and therapist are not in the same location due to particular restrictions, such as COVID-19 pandemic.